2020
DOI: 10.1111/cts.12895
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Review of Pharmacogenetic Testing at an Academic Children’s Hospital

Abstract: There is limited evidence to support pharmacogenetic (PGx) testing in children. We conducted a retrospective review of PGx testing among 452 patients at an academic children's hospital to determine the potential utility of PGx in diseases of childhood and to identify targets for future pediatric pharmacogenetic research. An actionable gene-drug pair associated with the 28 genes tested (Clinical Pharmacogenetics Implementation Consortium (CPIC) level A or B, Pharmacogenomics Knowledge Base (PharmGKB) level 1A o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…In 15.0% of cases the PGx results could be used for dose adjustment of at least one currently prescribed drug. The two most common gene‐drug diagnosis groups with matching clinical diagnosis and prescription were mood disorders and gastritis/esophagitis, and these are therefore considered promising targets for future studies in the area of PGx testing in children and adolescents 134 …”
Section: Genomics and Pgxmentioning
confidence: 99%
“…In 15.0% of cases the PGx results could be used for dose adjustment of at least one currently prescribed drug. The two most common gene‐drug diagnosis groups with matching clinical diagnosis and prescription were mood disorders and gastritis/esophagitis, and these are therefore considered promising targets for future studies in the area of PGx testing in children and adolescents 134 …”
Section: Genomics and Pgxmentioning
confidence: 99%
“…The National Institutes of Health–sponsored All of Us research program plans to enroll children and return pharmacogenomic results to participants 17 . Drugs with actionable pharmacogenomic dosing recommendations are frequently used in children 11,18 . Ramsey et al found that 7987‐10629 per 100 000 pediatric patients were exposed to at least 1 drug that the Clinical Pharmacogenetics Implementation Consortium (CPIC) strongly or moderately recommends a change in prescribing 11 .…”
Section: Pharmacogenomics In the Pediatric Clinic: Discovery And Implementation Of Dose Individualizationmentioning
confidence: 99%
“…About 50% of these drugs, either the whole class or individual drugs within these classes, have not been studied in children or have limited evidence of safety in pediatric populations. Extending these recommendations to the pediatric populations and adolescents remains controversial ( Neyro et al, 2018 ; Roberts et al, 2021 ; CPIC, 2022 ). Fortunately, efforts to better understand the potential utility for PGx implementation among the pediatric population are ongoing ( Namerow et al, 2020 ; Ramsey et al, 2021 ; Roberts et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Extending these recommendations to the pediatric populations and adolescents remains controversial ( Neyro et al, 2018 ; Roberts et al, 2021 ; CPIC, 2022 ). Fortunately, efforts to better understand the potential utility for PGx implementation among the pediatric population are ongoing ( Namerow et al, 2020 ; Ramsey et al, 2021 ; Roberts et al, 2021 ). Various models have been adopted by different institutes, from single gene to panels tested either preemptively or reactively while offering point of care electronic clinical decision support (eCDS) to clinicians ( Johnson et al, 2013 ; Haidar et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%